An algal sulfated galactan has an unusual dual effect on venous thrombosis due to activation of factor XII and inhibition of the coagulation proteases - Melo, Fábio R.; Mourão, Paulo A. S. (Thrombosis and Haemostasis, 2008)
Sulfated galactan from the red alga Botryocladia occidentalis has a potent anticoagulant activity,due to its ability to enhance thrombin and factor Xa inhibition by antithrombin and/or heparin cofactor II. It is less active than unfractionated heparin in arterial thrombosis,but in a venous thrombosis presents a dual effect,inhibiting thrombosis in low but not in high doses.This dual effect on venous thrombosis is a consequence of two actions, one that inhibits thrombin and factor Xa and one that induces factor XII activation. In order to dissociate these effects, we prepared derivatives of the sulfated galactan with low molecular weights. Two fractions that were similar in size to unfractionated heparin and low-molecular-weight heparin were obtained. As the molec- ular weight decreased, the ability to activate factor XII and to promote inhibition of coagulation proteases in the presence of antithrombin and heparin cofactor II diminished.At ∼5 kDa, the sulfated galactan fragment had no effect on factor XII activation, and showed the same effect as unfractionated heparin in a venous thrombosis model.The ∼5-kDa fragment is an antithrombotic with several advantages: i) It is as active as unfractionated heparin in venous thrombosis, but it has little activity in arterial thrombosis; ii) It inhibits venous thrombosis with very little anticoagulant effect; iii) It does not cause bleeding; and iv) It is not obtained from mammals.
Keywords: Sulfated polysaccharide; anticoagulant polysaccharide; antithrombotic polysaccharide; heparin; Hageman factor